RESEÑA de: Pérez Bowie, José Antonio (ed.). Gonzalo Torrente Ballester y el teatro. Vigo : Universidad de Vigo, 2013. - García-Abad García, M.ª Teresa (Signa: Revista de la Asociación Española de Semiótica, 2014)
-